Nilai-Nilai Pendidikan Melalui Kisah Dalam Al-QurâÄn - Lawati, Susi (BELAJEA: Jurnal Pendidikan Islam, 2016)
This study aimes to describe the stories in the Quran.Studyingit is in many things and so interesting. The wisdom behind these stories are full of educational value and can serve as guidelines for all education professionals, especially teachers at primary school level (SD).The lessons learned from the stories are highly relevant to children of primary school age (SD), so this study will briefly discuss the stories in the Quran, especially the story of the prophet Abraham, Joseph, Moses and Muhammad then analyzesthem and it can be obtained educational value.In a series of stories of the Quran contain instructive for human life as well as the methods of learning taught in an educational process.With the hope through learning the stories,it may be implicated in changes in student behavior, such as: strong motivation to move forward, raised awareness to carry out orders of religion, havinga good social attitude, being a good positive- thinking individual to God and to men, being critically, innovative, creative, realistic and logical